Proanthocyanidins suppress NLRP3 inflammasome and M1 macrophage polarization to alleviate severe acute pancreatitis in mice. Issue 2 (13th October 2022) - Sheng, Li‐Ping; Han, Chao‐Qun; Ling, Xin; Guo, Xian‐Wen; Lin, Rong; Ding, Zhen
Abstract: The role of reactive oxygen species (ROS) is crucial for the pathogenesis of acute pancreatitis (AP). Proanthocyanidins (PAs) have been confirmed to exert antioxidant activity. Our study aimed to determine whether PAs alleviated SAP via reducing ROS, suppressing NLRP3 inflammasome, and inhibiting M1 macrophage polarization. Our study investigated the protective effects of PAs on pancreatic histopathological injury using SAP mice. The effects of PAs on macrophages were investigated in inflammatory RAW 264.7 cells or mouse bone marrow‐derived macrophages (BMDMs) induced by lipopolysaccharide (LPS). Immunofluorescence staining and/or western blot assay were employed to evaluate NLRP3 inflammasome in macrophages and pancreatic tissue. Cell counting kit‐8 (CCK‐8) was used to access effects of PAs on cell viability and cytometry flow was used to determine the effects of the PAs on the ROS levels of the RAW 264.7 cells. Then, we evaluated M1 macrophage polarization using flow cytometry or real‐time quantitative polymerase chain reaction (RT‐qPCR). PAs administration alleviated pancreatic inflammation in SAP mice. The PAs depressed NLRP3 inflammasome and inhibited M1 macrophage polarization in pancreatic tissue. We also found that the PAs showed no cellular toxicity but decreased ROS levels in RAW 264.7 cells, downregulated the NLRP3 inflammasome in the macrophages, and inhibited cell M1 macrophage polarization. Our study indicates the anti‐inflammatory properties of the PAs on SAP mice by decreasing ROS levels, suppressing NLRP3 inflammasome, and M1 macrophage polarization.